Prevalence and Factors Associated with Under Nutrition among Children Aged 6 to 59 Months in Ngoma District, Rwanda - Dukuzimana, Marie Alice; Bizimana, Eric Gustave; Michael, Habtu; Habineza, Alphonse; Rutayisire, Erigene (Journal of Public Health International, 2021)
In Rwanda, 38% children aged 6-59 months are stunted. In Ngoma District, stunting rate is estimated at 41% among the children aged below 5 years. The study objective was to evaluate the prevalence and factors contributing to under nutrition among children aged 6- 59 months in Ngoma District. Cluster sampling was used to determine the study participants for each sector within 14 sectors by considering the sample size of 442. The WHO Anthro software version 3.2.2 was used to determine the nutritional status of the children. SPSS version 24 was used for analysis. Of 442 children participated in the study 50.9% of them were females, 24.4% were aged 15-23 months and the majority of children (89.8%) born with normal birth weight. Study findings revealed that the prevalence of under nutrition was 33.7% for stunting, 3.6% for wasting and 6.6% underweighted. Poor sanitation facility (AOR: 4.1, 95%CI: 1.83-9.3, p=0.001), poor diet (AOR: 1.9, 95%CI: 1.18-3, p=0.008) were significantly associated with stunting. Factors such as lack of hand-washing facilities (AOR: 2.5, 95% CI: 1.013-6.3, p=0.047), not eat vegetables (AOR: 4.4, 95%CI: 1.7-10.96, p=0.001), and not eat fishes (AOR: 4.1, 95%CI: 1.6-10.6, p=0.003) were associated with wasting. Short breastfeeding duration (AOR: 4.5, 95%CI: 2.9-7.2, p=0.001), not eat vegetables (AOR: 1.9; 95%CI: 1.1-3.05, p=0.008), and not eat eggs (AOR: 2, 95%CI: 1.3-2.9, p=0.001) were associated with underweight. Poor families with under-five children need continuous support that will assist them to improve nutritional status of their children.
Keywords: Under nutrition; Stunting; wasting; Underweight; Children aged 6-59 months; Ngoma district; Rwanda